(untitled) (Jurnal Mu’allim, 2026)
This study aims to examine the influence of the role of Islamic Religious Education (PAI) teachers in shaping students’ disciplinary character at SMAN 4 Kota Serang. The role of PAI teachers is essential in the educational process, particularly in character building through role modeling, habituation, and value internalization based on Islamic teachings. This research employed a quantitative approach with an associative research design. The research subjects consisted of 35 students. Data were collected through questionnaires, observations, and documentation. Data analysis was conducted using the Pearson Product Moment correlation test with the assistance of SPSS version 16.0. The results showed a positive and significant relationship between the role of PAI teachers and students’ disciplinary character, with a correlation coefficient of 0.436, which is higher than the r-table value at the 5% significance level. The coefficient of determination indicated that the role of PAI teachers contributed 19.0% to the formation of students’ disciplinary character, while the remaining 81.0% was influenced by other factors. Therefore, it can be concluded that the role of Islamic Religious Education teachers has a positive and significant influence on shaping students’ disciplinary character at SMAN 4 Kota Serang.